2011
DOI: 10.1007/s00464-011-1885-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of laparoscopy in the management of acute small-bowel obstruction: a review of over 2,000 cases

Abstract: Laparoscopy is a feasible and effective treatment for acute SBO with acceptable morbidity. Further studies are required to determine its impact on recurrent SBO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
98
1
18

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(122 citation statements)
references
References 42 publications
5
98
1
18
Order By: Relevance
“…Sin embargo, este concepto lentamente ha ido cambiando a medida que los cirujanos han ido adquiriendo más experiencia en habilidades laparoscópicas avanzadas, tal como ha ocurrido en otras patologías como el cáncer colorrectal 7 .…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Sin embargo, este concepto lentamente ha ido cambiando a medida que los cirujanos han ido adquiriendo más experiencia en habilidades laparoscópicas avanzadas, tal como ha ocurrido en otras patologías como el cáncer colorrectal 7 .…”
Section: Discussionunclassified
“…Éstas incluyen la abolición de la incisión de la laparotomía y su mayor período de recuperación postoperatoria, así como la disminución en la incidencia de hernias incisionales y de las adherencias postoperatorias 13,14 . En el caso de la OIB, la laparoscopía es una herramienta diagnóstica y terapéutica, evitando una laparotomía y sus consecuencias 7 . En aquellos pacientes en los cuales sea prudente y necesario la conversión a cirugía abierta, la laparoscopía permite que la incisión de la laparotomía pueda ser dirigida y limitada al sitio de la obstrucción, evitando así grandes incisiones 13 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Until present, no randomized controlled trial has been undertaken comparing laparoscopic and open adhesiolysis. However, many studies have tried to define the feasibility [63] and factors [64] [65]. Some recent studies have reported a higher success rate of around 75-90 % [66][67][68], but the number of patients were small (Table 4).…”
Section: Small Bowel Obstructionmentioning
confidence: 99%